KEHIDUPAN PASANGAN LESBIAN (Studi Kasus Di Kota Pekanbaru) - Sari, Erna Ratna; Bahri, Syamsul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Lesbian is terms of women who have a sexual orientation towards same sex. Lesbian is a sexsual behavior that deviates from the norms and values that apply. Nowanday, the lives that of people in big cities such as Pekanbaru, homoseksual phenomenon is growing and become unique to urban communities tend to be permissve (open-ended) against lesbian coples. This research aims to determine the physical and social characteristics as well as deviant sexual behavior in the city of Pekanbaru. the theory used in this reserch is the theory of deviantions, Theory of Behavior distorted (Deviant Behavior) by Robert K.Merton ( Elly M.Setiadi,2011). This study used a qualitative method, because the life of a lesbian couple is a social phenomenon that is unique in the life of society. Data is deone by using the technique of participant observation and in-depth interviews. Determination of informants is with Snow ball sampling to be recognized in depth the lives of lesbian couple. Qualitative data analysis is more emphasis on the meaning and symbols that arise from the behavior of a lesbian couple in their daily lives. From the findings of the field can be seen that in terms of the age of the dyke is only 19 years old to 23 years, the majority of students and Islamic religion. In this study, informants of six people, three men and three femme butch, in this study, they have a different experience in the prosess of becoming a lesbian. Factors affecting the informant into a dyke that is the pure sense of itself as a result of being hurt by a boyfriend or traumatized by men, because of the influence of poor families, and also influenced by the environment and the wrong friends so that bandwagon trying to be a lesbian.Keywords : Lesbian, Wrong Sex, and Diseases Society